PERHITUNGAN HARGA POKOK PENJUALAN VALAS - Muhammad Nuh (POLITEKNIK LP3I JAKARTA, 2014)
Given the increasingly irregular foreign exchange rate that occurred in Indonesia and there is often a foreign exchange differences on foreign currency happens to companies engaged in the Money Changer, due to the use of cost of goods sold calculation method is not in accordance with the rules of accounting. While the calculation of cost of goods sold is very influential over balance sheets and income statements are presented per period. Thus the author really need to raise the topic in this article titled